Analysis of The Effect of Profitability, Leverage and Firm Size on Firm Value - Heri Ispriyahadi; Budiman Abdulah (Kusuma Negara Business School, 2021)
This study examines profitability, leverage, and firm size on company value in the financial services sector. This study uses a sample of 67 companies in the financial industry (banks and non-bank financial institutions) listed on the Indonesia Stock Exchange. The sampling process was selected using purposive sampling by applying specific criteria. This study involves three regression estimations (pooled OLS, fixed effects, and random effects). Performing the Chow test, the Hausman test, and the Lagrange test shows that the Fixed Effect Model is the best in panel data regression. The results showed that ROA and company size have a significant relationship to firm value. Meanwhile, leverage shows a negative relationship but not substantial to firm value. These results illustrate that the higher the profit and the bigger the company gives a positive signal to investors, thus encouraging investors to buy company shares. Increasing investor demand encourages the increase in company value. The effect of the three independent variables (profitability, leverage, and company size) concurrently on the corporate value variable was recorded at 67.14%, and the remaining 22.86 influenced by other factors.